Răspuns :
∆=b^2-4ac-=9^2-4×2×10=81-80=1
X1=-b+∆ supra lu 2a=-9+1/2×2=-2
X2=-b-∆ supra 2a=-9-1/2×2=-2,5
X1=-b+∆ supra lu 2a=-9+1/2×2=-2
X2=-b-∆ supra 2a=-9-1/2×2=-2,5
a=2,b=9,c=10
delta=b^2-4ac=81-80=1>0
x1=(-b-radical din delta)/2a= (-9-radical din 1)/4=-10/4=-5supra 2
x2=(-b+radical din delta)/2a=(-9+radical din 1)/4=-8/4=-2
S={-5supra2,-2}
delta=b^2-4ac=81-80=1>0
x1=(-b-radical din delta)/2a= (-9-radical din 1)/4=-10/4=-5supra 2
x2=(-b+radical din delta)/2a=(-9+radical din 1)/4=-8/4=-2
S={-5supra2,-2}